Trichosporon asahii septic thrombophlebitis following lower extremity amputation in an immunocompetent host. (6th January 2018) - Mada, Pradeep Kumar; Ayoade, Folusakin; Li, Ailing; Todd, John
Abstract : A 59-year-old man with a history of peripheral vascular disease status post femoral popliteal bypass presented with critical limb ischaemia of the left leg. An arterial Doppler ultrasound showed an occluded graft requiring an above knee amputation. Five days after surgery, the patient developed fever, leucocytosis, significant stump swelling and pain, and serosanguinous discharge from his wound. Wound swab cultures from the stump grew Trichosporon asahii . A venous Doppler ultrasound revealed extensive thrombosis of the left lower extremity. Biopsy of the left thigh muscle showed necrotic thrombus with fungal hyphae in the clotted blood vessel. The left femoral vein was subsequently resected, and the excised venous tissue also grew T. asahii . The patient was successfully treated with voriconazole based on antifungal susceptibilities. This case describes an invasive fungal infection in the absence of typical immunosuppressive conditions commonly associated with Trichosporon spp. It also illustrates the role of a combination of antimicrobial and surgical management in achieving cure.